Mito e absurdo no moderno drama francês e em Nelson Rodrigues - Ceccagno, Douglas (2012)
This thesis aims at investigating, in its first part, how new meanings are produced through the use of Greek myths in the French drama between wars and during World War II, when France was under German occupation. The research focuses on the mythical plays of Jean Giraudoux, Jean Cocteau, Jean Anouilh and Jean-Paul Sartre, in which this dissertation analyzes the tensions between the feeling of absurdity, representative of the time of the two Great Wars and systematized by Albert Camus in The Myth of Sisyphus (1942), and the possibilities of Greek mythology to produce new meanings in a society where myths are reframed, other than those conveyed by the ancient literature, especially the Attic tragedy. Another aim is to propose a mythical interpretation, under the same perspective, to the four plays of the Brazilian writer Nelson Rodrigues written between 1945 and 1949. The comparison reveals differences of meaning in the reframed myths. Although they are written in the same period of time, the plays reflect societies with different historical backgrounds. The first chapter of the thesis discusses relevant concepts for analysis, as myth, tragic and absurd, as well as notions derived from the theory of imaginary. The second chapter, reserved to the study of French plays, examines historical and cultural transformations occurred in France in the 1930s and 1940s, and presents the analysis of the plays written by Giraudoux, Cocteau, Anouilh, and Sartre in the same period, with subjects taken from Greek mythology. The third chapter is devoted to Brazilian history and culture in the same decades, with special emphasis on the Brazilian theater of the period, and the role played by Nelson Rodrigues in this cultural context; and, in individual sections, the four mythical plays of this author are analyzed under the perspective of the reframing of Greek myths. Finally, the conclusion provides a comparison between the plays analyzed and the senses conveyed by the French and the Brazilian mythical drama at the same historical moment. This research is based on the theory of imaginary. Its main references are Gilbert Durand and Gaston Bachelard s writings, with the support, in a transdisciplinary perspective, of the researches on mythology done by Mircea Eliade and Joseph Campbell, and sources from historiography, philosophy and theatrical studies.